Roger Ebert's book of film - 4 0 16; Ebert, Roger; 5 (New York : W.W. Norton, 1997)
Collection of reviews and essays concerning actors and actresses, the early years of movies, various genres, directors, and screen writers.
Wilson's Public Library;Library Journal Starred;Publisher's Weekly
Adult;Adult
Keywords: 2 -- 0; 6; Motion pictures.;Motion pictures; 20; 2